Perichaena acetabulifera sp. nov. from Juarez City, Mexico. - Lizarraga Escobar, Marcos (2019)
Perichaena acetabulifera is described as a new species of myxomycete that fruited profusely in moist chamber cultures on bark samples collected from Populus deltoides and Ulmus pumila growing in urban areas of Juarez City, Chihuahua, Mexico. Photographs of its diagnostic macroscopic and microscopic features are provided.